The relative efficacy of imatinib, dasatinib and nilotinib for newly diagnosed chronic myeloid leukemia: a systematic review and network meta-analysis - Mealing Stuart (Experimental Hematology & Oncology, 2013)
Abstract Objectives Dasatinib 100 mg daily and nilotinib 600/800 mg daily have been compared to imatinib as first line treatments for CML in two recent randomised studies. However, no head to head evidence exists of the relative efficacy of dasatinib and nilotinib. Methods We conducted a systematic literature review and used the data extracted to perform an indirect comparison meta-analysis of the three interventions. Results Data from eight clinical studies (3,520 individuals) were included, all of which were of good quality (low risk of bias). At six months, the odds of complete cytogenetic response (CCyR) for dasatinib and nilotinib were approximately three times those for imatinib (range 2.77 to 3.06, all values not significant). At twelve months datatinib and nilotinib were significantly better than imatinib for both CCyR and major molecular response (MMR) (CCyR odds range 2.06 to 2.41, MMR odds range 2.09 to 2.87). At eighteen months dasatinib and nilotinib were again significantly better in terms of CCyR than imatinib (response odds 1.55 to 2.01). When dasatinib and nilotinib were compared to each other, for both clinical endpoints at all time points the response odds were not significantly different. Conclusions On the basis of a systematic review of the current literature base, dasatinib 100 mg, nilotinib 600 mg and nilotinib 800 mg should be viewed as equivalent in terms of complete cytogenetic and major molecular response.